Penerapan Model Realistic Mathematics Education (RME) untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa pada Materi Operasi Hitung Pecahan di Kelas V - Safrati Rizka; Novianti Novianti; Rahmi Wahyuni (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Elementary school students' mathematical problem-solving skills remain low, particularly regarding fraction operations. Students struggle to grasp fraction concepts and determine the steps needed to solve problems. This study aims to determine the improvement in students' problem-solving skills through the Realistic Mathematics Education (RME) model applied to the topic of fraction operations. The study employed a mixed-methods approach (combining quantitative and qualitative data) within a Classroom Action Research (CAR) framework, conducted at UPTD SD Negeri 9 Gandapura with 14 fifth-grade students. Data were collected via tests, observations, and interviews, and analyzed descriptively. The research was carried out in two action cycles, each comprising planning, implementation, observation, and reflection phases. The results indicate an improvement in problem-solving skills: the mastery percentage rose from 28.57% in Cycle I to 85.71% in Cycle II. Teacher activity increased from 79.99% in Cycle I to 90.76% in Cycle II, while student activity rose from 77.69% to 89.23%. Interview results show that students responded positively to the instruction, finding the material easier to understand through real-world contexts and the lessons more engaging. These findings indicate that the RME model is effective in enhancing students' mathematical problem-solving skills regarding fraction operations.